Al-Siyāsah al-Qanūnīyah li Ḥizb al-‘Adālah wa al-Rafāhīyah (Partai Keadilan Sejahtera/PKS) fi al-Fatrah 1998-2004 al-Mīlādī: Dirāsah li Qaḍīyat Qānūn Idārat al-Zakāh - Marzuki, Ismail (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2012)
This article discusses the politics of Islamic law of Partai Keadilan Sejahtera (Prosperity and Justice Party, PKS) 1998–2004 by analyzing the formulation of Law No. 38/ 1999 on Zakat Management, and Law No. 23/2011 on Zakat Management. It shows that there has been a shifting ideological expression in the evolution of the PKS that began to appear when this party morphed from Partai Keadilan (Justice Party) to PKS in 2002 because it had failed to pass the parliamentary threshold for the 1999 election, and had a practical political agenda for obtaining an increase of electoral votes. The ideological shift, among others, is shown through the process of the formulation of the Zakat Management Law which was influenced by several motives, among others ideological and practical political interests. PKS’s politics on Islamic law show that if its ideological interests contradict with its practical political interests, then the party opts for practical political interests.DOI: 10.15408/sdi.v19i3.357